Efeitos das alterações da temperatura muscular induzidas pela exposição aos ambientes quente e frio em relação ao desempenho dos sprints repetidos em cicloergômetro - Gustavo Guimarães Aguiar de Oliveira (2016)
This study investigates the effects of changes in muscle temperature (TMUSC) induced by exposure to hot and cold environments on the performance of repeated sprints (SRs) on a cycle ergometer. Thirteen physically active participants (24.4 ± 2.1 years; 80.6 ± 9.0 kg, 175.7 ± 3.9 cm) were exposed on different days, at environmental temperatures of 10, 26 and 42° C for 80 minutes. Further, the subjects performed 10 x 6-s all-out sprints with 30 s recovery between them. As expected, the exposure changed the body temperatures and heart rate (HR). At the end of 80 min exposure, the TMUSC was higher at 42° C compared to 26° C (37.3 ± 0.3 vs. 36.3 ° C ± 0.3 ° C) and 10 ° C ( 33.1 ± 1.6 ° C), and significantly lower at 10° C compared to 26 ° C (p <0.001). A similar response was observed for the mean skin temperature. The TRETAL was significantly higher at 42° C compared to 26° C and 10° C (p <0.001), but was not different between 10° C and 26° C (p = 0.388). HR was significantly higher at 42° C compared to 26° C and 10° C, and significantly lower at 10° C compared to 26° C. In relation to the physical performance, peak power and mean power presented by subjects were reducing during SRs for the three environments. The mean values of the peak and mean powers measured during the 10 SRs were lower at 10° C compared to 26° C and 42° C. In addition, when sprinting were evaluated separately, differences in peak and mean powers of subjects were observed, while the highest values were achieved at 42 C compared to the other two environment temperatures. There was a positive significant and moderate correlation between changes in muscle temperature and changes in peak power induced by the different environmental temperatures for the sprint 1 (r = 0.530; p = 0.005), but not for sprints 2 and 10. In conclusion, exposure to 42° C induced an increased in the TMUSC, while the exposure to 10° C reduced this temperature, contributing to physical performance in the first sprint was higher at 42° C in relation to other environments and the performance during the 10 SRs were lower at 10° C compared to other environments. Therefore, the results indicate that the effects of muscle warm-up on physical performance are transient, affecting performance only in the first sprint. On the other hand, the effects of muscle cooling on physical performance are more lasting and were observed during the 10 SRs.